Quadrilha junina paraense: valorização enquanto patrimônio cultural - MENDES, Heloisa do Socorro Martins (2019)
The work talk about Quadrilha Junina Dance, argue the possibility of its formalization as Intangible Cultural Heritage by the state of public policies. Explains the relevance and understanding of it as inducer of great participation of people and analyzes the participation of public management municipal and state in relation to strengthening and incentive in official events. Quadrilha Junina Dance, has foreign origin and came to Brazil in the century XIX, conquering the various social layers and is not restricted there are several appropriations and innovations that occurred, being cultivated by the population to the presente. The research was qualitative, it was first made participatory observation having as base Guimaraes (1975), shows that participation is one of the closest points to understand the other, bibliographical research and research in practice with three groups of Quadrilha Junina Dance: Sabor Açaí Junina (city of Belém), Coração Junino (city of Abaetetuba) e Revelação da Cremação Mirim (city of Belém), interviews was made (ROSA; ARNOLDI, 2006) whith five themes from two to five questions. Also were made interviews with Associação of Quadrilhas Juninas and Núcleo de Toadas do Pará (AQUANTO) and Federação Municipal of Quadrilhas Belém (FEMUQ). Moreover, also were made interviews with organs, Fundação Cultural of City Belém (FUMBEL), Fundação Cultural of Pará Tancredo Neves (CENTUR) and Fundação Cultural Abaetetubense and a visit to Instituto do Patrimônio Histórico Artístico Nacional (IPHAN) of Pará, to collect some material about the theme. The survey, about Quadrilha Junina Dance presents, beyong intangible cultural heritage, a social action involving benefits and contributions for children and teenagers from the peripheries of the neighborhoods and the place, valuing and recognising the dance as an integral part of the community.